1997
DOI: 10.1093/emboj/16.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Both the isomerase and chaperone activities of protein disulfide isomerase are required for the reactivation of reduced and denatured acidic phospholipase A2

Abstract: The spontaneous reactivation yield of acidic phospholipase A2 (APLA2), a protein containing seven disulfide bonds, after reduction and denaturation in guanidine hydrochloride is very low. Protein disulfide isomerase (PDI) markedly increases the reactivation yield and prevents the aggregation of APLA2 during refolding in a redox buffer containing GSH and GSSG. S‐methylated PDI (mPDI), with no isomerase but as nearly full chaperone activity as native PDI, has no effect on either the reactivation or aggregation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 37 publications
1
64
0
2
Order By: Relevance
“…These results suggested that the formation of disulfide bonds between PDI and CK contributed to the suppression of CK aggregation during refolding but was not the major driving force. DISCUSSION PDI has been demonstrated to act as a molecular chaperone independent of its isomerase activity (21)(22)(23)(24)(25), and it can exploit the synergy between these functions, especially when disulfide reshuffling is needed in the refolding of the substrates (3,26). Our results showed that WT PDI at high concentrations could act as a protector against aggregation but acted as an inhibitor of reactivation during CK refolding.…”
Section: Pdi Exhibits Both Anti-chaperone and Chaperone Activity Inmentioning
confidence: 63%
“…These results suggested that the formation of disulfide bonds between PDI and CK contributed to the suppression of CK aggregation during refolding but was not the major driving force. DISCUSSION PDI has been demonstrated to act as a molecular chaperone independent of its isomerase activity (21)(22)(23)(24)(25), and it can exploit the synergy between these functions, especially when disulfide reshuffling is needed in the refolding of the substrates (3,26). Our results showed that WT PDI at high concentrations could act as a protector against aggregation but acted as an inhibitor of reactivation during CK refolding.…”
Section: Pdi Exhibits Both Anti-chaperone and Chaperone Activity Inmentioning
confidence: 63%
“…PDI contains 2 CXXC (C, cysteine; X, any amino acid) active sites necessary for disulfide bond formation and isomerization. However, these sites are not essential for the molecular chaperone activity when PDI assists the refolding of client proteins that do not have a need for disulfide bond formation and isomerization (13). Based on its structural similarities, DsbA-L is categorized as a member of the PDI family.…”
Section: Dsba-l a Molecular Chaperone Or A Protein-folding Catalyst?mentioning
confidence: 99%
“…For PDI, the extent to which the chaperone and redox\isomerase activities are apparent in the folding of proteins is substrate-dependent, as is the degree of involvement of individual a or ah domains in redox\isomerase activity [69,79,[82][83][84]. Whereas chaperone activity has been shown for disulphide-containing proteins, such as lysozyme [85,86], and independence of the isomerase and chaperone activities has been shown in itro in the refolding of acidic phospholipase A # , glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and rhodanese [87][88][89], chaperone activity is lacking and does not seem to be required for folding of substrates such as antibody Fab fragments with intact disulphide bonds [90].…”
Section: Chaperone Functionmentioning
confidence: 99%